PENGARUH VARIABEL MAKRO EKONOMI TERHADAP RETURN SAHAM PADA JAKARTA ISLAMIC INDEX (JII) PERIODE 2013 -2020 - Prasetyo, Yuszril Teguh; Hariyani, Happy Febrina (Journal of Financial Economics & Investment, 2022)
This study aims to determine the effect of macroeconomic variables including BI-rate, exchange rate, and Gross Domestic Product Development on stock returns of the Jakarta Islamic Index. The analytical method used in this study uses panel data regression analysis. The coefficient of determination (R2) obtained an R-Squared value of 0.233956 or 23.39%. The result of this research is that the BI-rate has a significant negative effect on JII's stock returns. The exchange rate has a significant negative effect on JII's stock returns. And the development of Gross Domestic Product has a significant positive effect on JII's stock returns.